Middle powers as 'peacemaking entrepreneurs' in Myanmar's peace process 2011–2021. - Roy, Chiraag; Ware, Anthony; Laoutides, Costas (Pacific Review, 2024)
Middle powers were visible actors in Myanmar's peace-donor landscape, from the beginning of that country's peace process in 2011 until the 2021 coup. Considering Myanmar's longstanding dependency on China and generally difficult relationship with larger powers, this appears to be significant. However, the literature on middle powers remains incapacitated by a definitional opacity that makes application of the term difficult, despite consistent references to their mediating capabilities. Recent scholarship has applied an 'entrepreneurial' lens to understanding middle power behaviour, implying middle powers are driven by a confluence of material and ideational factors. Based on fieldwork interviews with over fifty informants examining Norwegian, Japanese and Australian engagement with peacemaking in Myanmar 2011–2021, this paper expands on the entrepreneurial label and argues that middle powers in Myanmar acted as peacemaking entrepreneurs—as actors that traded upon their peacemaking reputations to secure concomitant material benefits. Nevertheless, this paper argues that engaging in peacemaking entrepreneurship proved to be problematic in Myanmar's context, given it tended to favour incumbent power. Indeed, in stark contrast to theoretical assumptions of these actors as neutral intermediaries, this paper raises serious questions about the contribution of middle powers in peacemaking.